2023
DOI: 10.1111/aogs.14668
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term consequences of juvenile vulvar lichen sclerosus: A cohort study of adults with a histologically confirmed diagnosis in childhood or adolescence

Beth Morrel,
Irene A. M. van der Avoort,
Patricia C. Ewing‐Graham
et al.

Abstract: IntroductionVulvar lichen sclerosus (VLS) occurs in at least one in 900 girls. There is limited knowledge as to what extent the disease persists in adulthood and what the repercussions in adulthood may be. The aim of this study is to evaluate the long‐term consequences of VLS diagnosed in childhood or adolescence.Material and methodsThe population of females histologically diagnosed with VLS in childhood or adolescence in the Netherlands between 1991 and 2015 was identified through the national pathology datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Table 1 shows the included publications listed chronologically, describing the study, the questionnaires applied and outcome measures with the corresponding (C)OD 14 . Of the 35 studies included, 5–10,16–44 14 16–21,25–28,33–36 developed a new scoring system or questionnaire. Twenty-six different tools were found, and 4 different ODs identified: QoL, symptoms, clinical (visible) signs, emotional impact, and sexual functioning.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 shows the included publications listed chronologically, describing the study, the questionnaires applied and outcome measures with the corresponding (C)OD 14 . Of the 35 studies included, 5–10,16–44 14 16–21,25–28,33–36 developed a new scoring system or questionnaire. Twenty-six different tools were found, and 4 different ODs identified: QoL, symptoms, clinical (visible) signs, emotional impact, and sexual functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Six questionnaires that had been applied just once in VLS research were found, the EQ-5D VAS † , 5 Short Form-12 (SF-12), 5 Short-Form-36 (SF-36), 24 WHO-5 d, 9 WPAI:GH, d and PHQ-9 d, 42 The subtypes QoL-dermatologic and QoL-vulvar cover the QoL-LS specific COD. Within this domain 4 questionnaires, the Skindex-29, 5,6,43 DLQI, 7,9,30,41,43 DSQL-V d , 16 and Vulvar Quality of Life Index (VQLI) 10,31,33,37,38,44 have been applied to VLS. Of these questionnaires the DLQI, which is a QoL-dermatological specific questionnaire, and the VQLI, a QoL-vulvar specific questionnaire, were used most often respectively 5 and 6 times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations